Precipitation variations recorded in tree rings from the upper Salween and Brahmaputra River valleys, China - Mary Gagen (Ecological Indicators, 2020)
The spatio-temporal variations of precipitation in the Tibetan Plateau (TP) have vital impacts on fresh water resources, and therefore the sustainable development, over a large part of Asia. Extending instrumental records of precipitation in the regional trans-boundary river basins is critical for resource managers and policy-makers to manage finite water resources in the region under climate change. Here we reconstruct precipitation variations from prior September to current June (r2 16 = 43%, 1600-2016 CE) in the upper Salween River valley and from prior July to current April (r2 17 = 44%, 1650-2016 CE) in the upper Brahmaputra River valley based on tree ring width variations in conifer tree rings from the Salween and Brahmaputra River basins. Correlation analysis reveals precipitation variations in the two river basins to co-vary over the past 367 years, and a wetting trend is revealed from the 1970s. Spatial correlation analyses with gridded precipitation data extends the reconstruction across the southern Tibetan Plateau. The first eigenvector of our ring width chronologies, and that of other precipitation-sensitive tree ringrecords from nearby areas successfully captures instrumental streamflow 23 variability in the two river basins. Over the past 3 decades, rapid socio-economic development and population growth in southern and southeastern Asia has pressured the water resource supply of the Tibetan Plateau. Our precipitation reconstructions provide valuable insight for strategies to manage these vital regional water resources.